2008
DOI: 10.1073/pnas.0804918105
|View full text |Cite
|
Sign up to set email alerts
|

The Fezf2–Ctip2 genetic pathway regulates the fate choice of subcortical projection neurons in the developing cerebral cortex

Abstract: Pyramidal neurons in the deep layers of the cerebral cortex can be classified into two major classes: callosal projection neurons and long-range subcortical neurons. We and others have shown that a gene expressed specifically by subcortical projection neurons, Fezf2, is required for the formation of axonal projections to the spinal cord, tectum, and pons. Here, we report that Fezf2 regulates a decision between subcortical vs. callosal projection neuron fates. callosal ͉ cell fate ͉ zinc finger transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
368
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 313 publications
(395 citation statements)
references
References 33 publications
(76 reference statements)
22
368
2
Order By: Relevance
“…2 I and J), consistent with the interpretation (Fig. S1B) that at least some neurons that normally express Fezf2 acquire a callosal identity in the absence of Fezf2, possibly owing to acquisition of Satb2 expression (8).…”
Section: Visualization Of Callosal and Subcortical Axonal Connectionssupporting
confidence: 88%
See 2 more Smart Citations
“…2 I and J), consistent with the interpretation (Fig. S1B) that at least some neurons that normally express Fezf2 acquire a callosal identity in the absence of Fezf2, possibly owing to acquisition of Satb2 expression (8).…”
Section: Visualization Of Callosal and Subcortical Axonal Connectionssupporting
confidence: 88%
“…2 A and E) and thalamus (Fig. S4I), whereas labeled axons are absent from the CC, as previously described (8,11). At P0, PLAP + axons descend subcerebrally and branch toward the thalamus (Fig.…”
Section: Visualization Of Callosal and Subcortical Axonal Connectionssupporting
confidence: 78%
See 1 more Smart Citation
“…Several studies have demonstrated that the fate specification and differentiation of CSMN are under the control of a combinatorial set of transcription factors that can either induce or inhibit CSMN-specific genes during corticogenesis (8,9,21,28,29). In the present study, we provide evidence that COUP-TFI is an upstream negative regulator of a CSMN differentiation program in corticofugal neurons, through repression of a genetic program of CSMN differentiation.…”
Section: Coup-tfi Is a Negative Regulator Of A Genetic Csmn Differentsupporting
confidence: 59%
“…It is likely that abnormal expression of corticothalamic neuron genes during CSMN differentiation, and dysregulation of CSMN "control genes" centrally contribute to improper differentiation of these neurons. In support of this latter hypothesis, ectopic expression of Fezf2 and CTIP2 leads to altered axonal trajectories (6,28), and dose-dependant effects of CTIP2 on CSMN differentiation have been reported (4,8). indicating that precise levels of CSMN-specific genes are a fundamental requisite for correct differentiation of corticofugal neurons.…”
Section: Coup-tfi Is a Negative Regulator Of A Genetic Csmn Differentmentioning
confidence: 76%